2019
DOI: 10.1111/iju.14078
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein/albumin ratio is a predictive factor for prognosis in patients with metastatic renal cell carcinoma

Abstract: Objectives To evaluate the effect of pretreatment C‐reactive protein/albumin ratio and modified Glasgow prognostic score on the prognosis in patients with metastatic renal cell carcinoma. Methods A retrospective study was carried out in 176 patients with metastatic renal cell carcinoma who received first‐line tyrosine kinase inhibitors. The effect of adding inflammatory prognostic scores to the International Metastatic Renal Cell Carcinoma Database Consortium model (International Metastatic Renal Cell Carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The main reason might be the short follow‐up periods and the regional bias in Japan. Approximately 1.5‐fold longer median survival time has been reported in previous studies in Japan than in North America or Europe 14,15,17–22 . Health insurance systems and racial differences could be possible reasons.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The main reason might be the short follow‐up periods and the regional bias in Japan. Approximately 1.5‐fold longer median survival time has been reported in previous studies in Japan than in North America or Europe 14,15,17–22 . Health insurance systems and racial differences could be possible reasons.…”
Section: Discussionmentioning
confidence: 82%
“…Approximately 1.5-fold longer median survival time has been reported in previous studies in Japan than in North America or Europe. 14,15,[17][18][19][20][21][22] Health insurance systems and racial differences could be possible reasons. The public health insurance system for its citizens in Japan covers almost every standard treatment, including surgery, targeted therapy and immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, several prognostic markers for axitinib treatment have been suggested, such as NLR 25 , serum albumin level 26 , serum lactate dehydrogenase level 26 , and serum CRP level 27 , among others. However, the model-development cohorts for these studies consisted of heterogeneous populations that included patients who had received a variety of treatments, including several VEGFR-TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 570 records, identified irrelevant by title and abstract screening, were excluded; and the remained 47 records, which investigated the correlation between CRP/Alb reactivity and survival outcomes of patients with RCC, were evaluated in full text. To meet our inclusion and exclusion criteria, six articles of five literatures [21][22][23][24][25] were eligible and eventually included in our study for analysis of the relationship between CRP/Alb and outcomes of the RCC patients. Our work flowchart is shown in Fig.…”
Section: Study Characteristicsmentioning
confidence: 99%